An English course - Walker, Michael, 1942-; Barrett, Jack (Jack C.) (Reading, Mass. : Addison Wesley Pub. Co., 1984)
English lessons for the foreign speaker, consisting of short readings with follow-up questions and activities.
Keywords: English language -- Textbooks for foreign speakers; English language -- Textbooks for foreign speakers